Effect of foreign microenterprises on the economy-social of the people in Kaysone Phomvihane city, Savannakhet province - MANIVONG, Khamkeo; SACBOUAVONG , Khoune; XOMVIMANE, Khamphanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purposes of this research were to study the effect of foreign micro-enterprises on the economy-social status of the people in Kaysone Phomvihane. The effect is divided into three areas: economic effect, social-cultural effect and environmental effect. The sample group used in the study was 381 families in Kaysone Phomvihan city, Research tools using questionnaires, the statistics used in the data analysis are to analyze the mean, percentages and standard deviations using SPSS software. The study found that: The effect of foreign micro-enterprises on the economy as a whole is moderate with average and standard deviation equal to (X ̅ = 3.20; S.D = 1.01), among them the effect on job creation of people is more prominent than other factors because when foreign entrepreneurs do business in the same sector will affect the creation of jobs for people. The effect of foreign micro-enterprises on the overall cultural-social effect was moderate with the mean and standard deviation equal to (X ̅ = 3.05; S.D = 1.14), the effect on the security of life and property is on many levels because when foreign entrepreneurs do business in the city foreign employees who bring business do the opportunity to do bad things such as property fraud, stealing, opening brothels and gambling that damage the fine traditions of Laos. The effect of foreign micro-enterprises on the overall environment is large, with average values and standard deviations equal to (X ̅ = 3.64; S.D = 1.12), the impact of waste generation in society is increasing due to the increase in the number of foreign entrepreneurs doing business, the locals cannot cover the waste from local businesses and abroad contamination of soil, water and air pollution may result in inequality in the city and the health of the people. In conclusion, foreign micro-enterprises have a positive effect as people have used goods and services and learned business things from foreign enterprises and the negative effect has made local businesses unable to compete with foreign businesses, creating environmental pollution and environmental pollution.